Modelling the effect of intervillous flow on solute transfer based on 3D imaging of the human placental microstructure. (December 2017) - Perazzolo, S.; Lewis, R.M.; Sengers, B.G.
Abstract: Introduction: A healthy pregnancy depends on placental transfer from mother to fetus. Placental transfer takes place at the micro scale across the placental villi. Solutes from the maternal blood are taken up by placental villi and enter the fetal capillaries. This study investigated the effect of maternal blood flow on solute uptake at the micro scale. Methods: A 3D image based modelling approach of the placental microstructures was undertaken. Solute transport in the intervillous space was modelled explicitly and solute uptake with respect to different maternal blood flow rates was estimated. Fetal capillary flow was not modelled and treated as a perfect sink. Results: For a freely diffusing small solute, the flow of maternal blood through the intervillous space was found to be limiting the transfer. Ignoring the effects of maternal flow resulted in a 2.4 ± 0.4 fold over-prediction of transfer by simple diffusion, in absence of binding. Villous morphology affected the efficiency of solute transfer due to concentration depleted zones. Interestingly, less dense microvilli had lower surface area available for uptake which was compensated by increased flow due to their higher permeability. At super-physiological pressures, maternal flow was not limiting, however the efficiency of uptake decreased. Conclusions: This study suggests that the interplay between maternal flow and villous structure affects the efficiency of placental transfer but predicted that flow rate will be the major determinant of transfer. Highlights: 3D image based computational modelling of the placental microstructure. First image-based model combining maternal intervillous flow and solute transport. Local maternal flow conditions are important for placental solute transfer.